Design of fixed-point smoother algorithm for linear discrete time-delay systems - Zhao, Hongguo; Cui, Peng; Guo, Xiaochun (Journal of control theory and applications, 2012)
This paper investigates the fixed-point smoothing problems for linear discrete-time systems with multiple time-delays in the observations. The linear discrete-time systems considered have 1 ＋ 1 output channels. One is instanta- neous observation and the others are delayed. The fixed-point smoothers involving recursive algorithm and non-recursive algorithm are designed by using innovation analysis theory without relying on the system augmentation approach. Also, it is further shown that the design of fixed-point smoother comes down to solving 1 ＋ 1 Riccati equations with the same dimensions as the original systems.